The meaningful change threshold as measured by the 16-item quick inventory of depressive symptomatology in adults with treatment-resistant major depressive and bipolar disorder receiving intravenous ketamine. - McIntyre, Roger S.; Lipsitz, Orly; Lui, Leanna M.W.; Rodrigues, Nelson B.; Gill, Hartej; Nasri, Flora; Ling, Rui; Teopiz, Kayla M.; Ho, Roger C.; Subramaniapillai, Mehala; Kratiuk, Kevin; Mansur, Rodrigo B.; et al. (Journal of Affective Disorders, 2021)
Objective: .To identify a meaningful change threshold (MCT) in depression outcomes in adults with treatment-resistant major depressive disorder (MDD) or bipolar disorder (BD) receiving intravenous ketamine treatment at a community-based mood disorders center.Method: .A triangular approach integrating both anchor-based and distributive methods was used to identify meaningful change on the patient-reported Quick Inventory for Depressive Symptoms Self-Report 16-Item (QIDS-SR16) as associated with the Patient Global Impression - Severity (PGI-S). Both the QIDS-SR16 and the PGI-S are self-report measures, and were collected at five timepoints (timepoints were approximately 2-7 days apart).Results: .A total of 297 adults with treatment-resistant depression (TRD) as part of either DSM-5-defined MDD or BD were included. The MCT for the QIDS-SR16 revealed that a mean improvement of 3.38 points from baseline was comparable to a 1-point improvement on the PGI-S. Together with an examination of the probability density function, a 3.5-point change is a reasonable MCT (i.e., 1-point PGI-S improvement) for the QIDS-SR16. A 2-point symptomatic improvement on the QIDS-SR16 was associated with no change on the PGI-S.Conclusion: .A 3.5-point reduction in the QIDS-SR16 represents a MCT based on the PGI-S for adults with treatment-resistant MDD or BD receiving intravenous ketamine treatment at a community-based mood disorders center. These findings are limited by the post-hoc nature of this analysis and open-label case-series design. Measurement-based care decisions by patients, providers and clinicians, as well as cost/reimbursement decisions should include consideration of meaningful change along with conventional objective outcomes.